Pengaruh Kualitas Pelayanan Terhadap Kepuasaan Pasien BPJS Poli Penyakit dalam Rumah Sakit Bhayangkara Pontianak - Saputro, Anton Hadi; Rochmawati, Ida; Saleha, Eha (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
A hospital is a public facility owned by the government or private sector which has a very strategic role in efforts to improve public health services. The new paradigm of health services requires hospitals to provide quality services according to patients' needs and desires while still referring to professional and medical codes of ethics. Quality is the core of the survival of an institution. Therefore, hospitals are required to always maintain consumer trust by improving service quality so that consumer satisfaction increases. This study aims to analyze the influence of service quality on patient satisfaction at Bhayangkara Hospital, Pontianak City. The research method used in this research is a quantitative method to determine the quality of service that has the greatest impact on community satisfaction. Samples were taken from 95 patients. Data collection techniques use observation and questionnaires. The results of the research show that the influence of service quality on BPJS patient satisfaction in internal medicine poly health services at Bhayangkara Hospital, Pontianak, most of the respondents are in the satisfactory category and a small number of respondents are in the unsatisfactory category. The results of this research show that service quality, which consists of the variables reliability (X1), responsiveness (X2), assurance (X3) and empathy (X5), has a significant effect on patient satisfaction, while the tangibles variable (X4) has no significant effect. Then the variable with the most dominant influence on patient satisfaction is the empathy variable (X5). And to improve service quality, researchers hope that Bhayangkara Hospital will test these variables, especially those that have a negative influence (tangibles X4) so that they can comply with the rules and mechanisms for improving service quality on patient satisfaction. The researcher's advice to Bhayangkara Pontianak Hospital is that nurses at Bhayangkara Pontianak Hospital should be able to maximize services according to the promised time, increase trust and responsiveness to patient complaints, and pay attention to the physical facilities of the Bhayangkara Pontianak Hospital Internal Medicine Clinic.